Immune Checkpoint Inhibitor Toxicity in Head and Neck Cancer: From Identification to Management - Wang, Haiyang; Mustafa, Abdulkadir; Liu, Shixi; Liu, Jun; Lv, Dan; Yang, Hui; Zou, Jian (Frontiers in Pharmacology, 2019)
Benefited from the continuously clarifying underlying biology of immune checkpoints and ligands-receptors interactions, the emergence of new anti-cancer treatment strategy -- immunotherapy has showed substantial benefits on several liquid and solid tumors. Immune checkpoint inhibitors (ICIs) can block the negative regulatory components and enhance the T-cell function, thus let to prominent anti-cancer activity. On account of its promising effect on various malignancies that showed in the clinical trials, ICIs have been considered to be the most potent anti-cancer agents in the near future. Head and neck cancer is the 7th common neoplasm worldwide and the gross 5-year survival rate was only 60%. Managing locoregionally advanced, recurrent or metastatic head and neck tumors were still the challenging problems for both oncologists and surgeons. Recent clinical trials employing the immune-modulating antibodies that target cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) and programmed cell death-1 (PD-1) herald a new era of anti-cancer therapy. However, like all other anti-cancer drugs, ICIs also have side effects while upregulating the immune system to enhance antitumor response, which was known as immune-related adverse events (irAEs). Generally, most irAEs were transient, but sometimes they can cause serious organ dysfunction, even fatal. In addition, due to the distinct anatomical feature, advanced head and neck tumors often affect the upper aerodigestive track and cause serious dyspnea or dysphagia. Toxicities of ICIs may more lethal for such patients. Thus, as the increasing application of anti-checkpoint agents in head and neck cancer, there is urgent need to ascertain the safety of this novel treatment strategy. Here we compile this review of existing clinical trials on toxicity of ICIs during cancer treatment. The particular clinical manifestation, characteristics of complication development in fatal cases and the management strategies were discussed. This may provide vital information for future oncology trials and clinical practice.